2019
DOI: 10.1002/ijc.32557
|View full text |Cite
|
Sign up to set email alerts
|

Resorting the function of the colorectal cancer gatekeeper adenomatous polyposis coli

Abstract: As a large number of cancers are caused by nonsense mutations in key genes, read‐through of these mutations to restore full‐length protein expression is a potential therapeutic strategy. Mutations in the adenomatous polyposis coli (APC) gene initiate the majority of both sporadic and hereditary colorectal cancers (CRC) and around 30% of these mutations are nonsense mutations. Our goal was to test the feasibility and effectiveness of APC nonsense mutation read‐through as a potential chemo‐preventive therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…To rule out a nonspecific effect on cell proliferation and confirm that the increased Cyclin-D1 levels observed upon DHX29 KO can be specifically attributed to Wnt signaling regulation, we tested the levels of proliferation in this cell line. Proliferation was tested using Ki-67, a proliferative marker strongly linked to cell cycle control [ 19 ]. NT1 and DHX29 KO cell lines were fixed and stained with a Ki-67 specific antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To rule out a nonspecific effect on cell proliferation and confirm that the increased Cyclin-D1 levels observed upon DHX29 KO can be specifically attributed to Wnt signaling regulation, we tested the levels of proliferation in this cell line. Proliferation was tested using Ki-67, a proliferative marker strongly linked to cell cycle control [ 19 ]. NT1 and DHX29 KO cell lines were fixed and stained with a Ki-67 specific antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a clinical trial, ten patients with FAP and APC nonsense mutations were given erythromycin for 4 months and had endoscopies at baseline, 4 months, and 12 months after treatment. 149 Results indicated that the number of adenomas and cumulative and maximal polyp size decreased. Tissue samples were also collected for assessment and were then molecularly and genetically analyzed.…”
Section: Targeting Apc In the Clinical Settingmentioning
confidence: 98%
“…Treatment not only reduced the number of somatic APC mutations, but also restored APC gene function and decreased cellular proliferation. 149 …”
Section: Targeting Apc In the Clinical Settingmentioning
confidence: 99%
“…If read-through in eukaryotes is due to an interference with mitochondrial functions only has not been addressed. Nevertheless, a clinical study investigating the efficacy of erythromycin treatment for read-through of APC gene stop codon mutations in familial adenomatous polyposis has been initiated [247] and the impact of macrolides on stop codon read-through has been proven in proand eukaryotic species as well as patients (Table 1) [242,[248][249][250][251][252][253].…”
Section: Macrolidesmentioning
confidence: 99%